Influence of different behavioural factors and obesity status on systolic blood pressure among pre-school children. (November 2014) - Mota, J.; Silva-Santos, S.; Barros, M.; Farias Júnior, J. C.; Vale, S.
Abstract Aim: The aim of this study was to examine the association between sleeping time (SLT), time spent using screen (ST) and weight status with Systolic Blood Pressure (SBP) among pre-school children. Subjects and methods: The sample comprised 628 pre-school children (50% female), aged 3–6 years-old. SLT and ST were reported by parents. BMI values were categorized according to IOTF. SBP cut points were based on SBP percentiles for age, sex and height. ST was dichotomized according to the following criteria: ≤1 hour vs >1 hour and SLT: ≤10.5 hours vs >10.5 hours. Participants were then categorized into one of four category profiles: Low ST/High SLT; High ST/Low SLT; Low ST/Low SLT and High ST/High SLT. Results: Children assigned to the High ST/Low SLT group were 2-times more likely to have high SBP values compared to those who were assigned to the Low ST/High SLT group (OR = 2.4; 95% CI = 1.1–5.1). Furthermore, those who were assigned as overweight and obese were more likely to be classified as having elevated BP (OR = 1.8; 95% CI = 1.1–3.2 for overweight and OR = 3.1; 95% CI = 1.6–5.8 for obese, respectively). Conclusion: The data showed that high ST exposure time and low SLT are associated with enhanced blood pressure in children at pre-school.